The writing in the stars : a jungian reading of the poetry of Octavio Paz - Williamson, Rodney, 1948- (University of Toronto romance series., 2007)
The Writing in the Stars explores Paz's life and ideas by establishing a dialogue between the structure and recurring images of his major poems and the ideas of Carl Jung.